The Experience of Breastfeeding Intention among Adolescent Mothers - Khoonphet, Chudanut; Kala, Sasikarn (Princess of Naradhiwas University Journal, 2019)
This descriptive phenomenology research aimed to explore experience intention of breastfeeding among adolescent mothers at the hospital center in Songkhla. Fifteen participants were selected by a purposive sampling method. The participants included 15-19 years old. Data were collected by in-depth interview and analyzed with link of experience of breastfeeding intention until theme emerges. The finding found three themes: 1) factors that cause intention, 2) the process of intention, and 3) result of intent. These findings will be useful for appropriate assistance and support to success in breastfeeding of postpartum adolescent mothers.